Recruiting a Hard-to-Reach, Hidden and Vulnerable Population: The Methodological and Practical Pitfalls of Researching Vaccine-Hesitant Parents - Hilário, Ana Patrícia; Scavarda, Alice; Numerato, Dino; Mendonça, Joana; Cardano, Mario; Marhankova, Jaroslava; Gariglio, Luigi; Vuolanto, Pia; Anderson, Alistair; Auvinen, Petra; Bracke, Piet; Douglass, Tom; et al. (Qualitative health research, 2023)
While recruitment is an essential aspect of any research project, its challenges are rarely acknowledged. We intend to address this gap by discussing the challenges to the participation of vaccine-hesitant parents defined here as a hard-to-reach, hidden and vulnerable population drawing on extensive empirical qualitative evidence from seven European countries. The difficulties in reaching vaccine-hesitant parents were very much related to issues concerning trust, as there appears to be a growing distrust in experts, which is extended to the work developed by researchers and their funding bodies. These difficulties have been accentuated by the public debate around COVID-19 vaccination, as it seems to have increased parents' hesitancy to participate. Findings from recruiting 167 vaccine-hesitant parents in seven European countries suggest that reflexive and sensible recruitment approaches should be developed.
Keywords: vakcíny; Vulnerable Populations; Vaccines; Humans; Health Knowledge, Attitudes, Practice; zranitelné populace; COVID-19 Vaccines; Parents; zdraví - znalosti, postoje, praxe; vakcíny proti COVID-19; Patient Acceptance of Health Care; pacientův souhlas se zdravotní péčí; vakcinace; Vaccination; lidé; rodiče